Potential of Reducing CO2 Emission Using Parabolic Trough Collector for 13.75MW Desalination Processes - I Putu, Arya Krisnatama; Mursid, Sri Paryanto; Widarti, Sri (Department of Chemical Engineering, Politeknik Negeri Bandung, 2023)
Desalination is an important process in fulfilling the freshwater demands of both the industrial sector and human needs. Typically, thermal desalination processes rely on fossil fuels to minimize production costs. However, using fossil fuel in desalination contributes to releasing CO2 emissions into the atmosphere. Therefore, it is essential to utilize renewable energy sources to mitigate the production of CO2 emissions. To reduce CO2 emissions research has been conducted to explore the potential use of parabolic trough solar collectors in harnessing available solar energy at the power plant site for thermal desalination processes which required 13.75 MW of thermal energy. The study utilized the system advisor model software to assess the collector’s system performance. The research findings indicate that 416 units of parabolic trough solar collectors are required to fulfill the thermal power needs. The presence of these solar collectors has the potential to generate 26.06 GWh of thermal power, thereby reducing coal consumption by 5,740.4 metric tons per year and directly lowering CO2 emissions by 13,892 metric tons per year.